Remimazolam in Modern Anaesthesia Practice: From Pharmacokinetics to Clinical Outcomes - Kateel, Ramya; Bhat, Ravitej (Current Drug Therapy, 2025)
Remimazolam, a novel ultra-short-acting benzodiazepine, has emerged as a promising agent in the field of anaesthesia and sedation. This comprehensive review examines the pharmacological properties, clinical applications, and safety profile of remimazolam. Its unique pharmacokinetic profile, characterised by rapid onset and offset of action, organ-independent metabolism, and availability of a specific reversal agent, offers potential advantages over traditional sedatives. Clinical studies have demonstrated its efficacy in procedural sedation, particularly in gastrointestinal endoscopy and bronchoscopy, as well as in the induction and maintenance of general anaesthesia. Emerging evidence also suggests its potential utility in intensive care sedation. Remimazolam has shown a favourable safety profile, with studies indicating comparable or improved hemodynamic stability and potentially reduced respiratory depression compared to propofol. The availability of flumazenil as a reversal agent enhances its safety profile. However, as with any relatively new medication, ongoing research is needed to fully characterise its long-term safety and optimal use in various clinical scenarios. This review synthesises current knowledge on remimazolam, providing insights into its potential to optimise sedation and anaesthesia practices across diverse patient populations and clinical settings, while highlighting areas for future research.
Keywords: new anaesthetic agent